The A54T polymorphism in the FABP2 gene and its relationship with obesity (2020)
Introduction: Obesity is a complex, multifactorial, and mostly preventable disease affecting, along with overweight, more than a third of today’s world population. Variations in the nucleotide sequence of both metabolic and appetite control genes have been counted among these non-modifiable factors and are associated with BMI, lipidic profile, and abdominal circumference alterations. Methods: An analytical, non-experimental, and transversal research was done with the purpose to assess the presence of A54T polymorphism in the FABP gene in a sub-sample from the Maracaibo City Metabolic Syndrome Prevalence Study. Results: 154 individuals eight subjects were carriers of the A54Tpolymorphism, namely, a genotypic frequency of 5.19 %, with a sex distribution of 50 % for women (n=4) and 50 % (n=4) for men. In respect of alleles similarity degree, 75 % (n=6) were homozygous, and 25 % (n=2) were heterozygous. Obesity diagnosis throughout BMI was only present in 12.50 % (n=1) of the A54T carriers. Conversely, 25 % (n=2) of the carriers were overweighed; 50 % (n=4) were presented as normal-weight people; and only 12.50 % (n=1), in one underweighted person. Conclusion: As in many other studies, we do not find an association between Ala54Thr polymorphism and obesity. This result reinforces the fact of the multifactorial character of these diseases and a carrier state of this polymorphism is not necessarily to experience a higher obesity risk, at least, in our environment.